Quantitative Analysis of Interaction Between CADM1 and Its Binding Cell-Surface Proteins Using Surface Plasmon Resonance Imaging - Ito, Takeshi; Kasai, Yutaka; Kumagai, Yuki; Suzuki, Daisuke; Ochiai-Noguchi, Misaki; Irikura, Daisuke; Miyake, Shiro; Murakami, Yoshinori (Frontiers in Cell and Developmental Biology, 2018)
The cell adhesion molecule (CADM) family of the immunoglobulin superfamily (IgSF) comprises four members, CADM1–CADM4, and participates in the formation of epithelial and synaptic adhesion through cell–cell homophilic and heterophilic interactions. To identify the partners that interact with each member of the CADM family proteins, we set up a platform for multiple detection of the extracellular protein–protein interactions using surface plasmon resonance imaging (SPRi) and analyzed the interactions between the CADM family proteins and 10 IgSF of their structurally related cell adhesion molecules. SPRi analysis identified a new interaction between CADM1 and CADM4, where this heterophilic interaction was shown to be involved in morphological spreading of adult T-cell leukemia cells expressing CADM1 when incubated on CADM4-coated glass. Moreover, class-I MHC-restricted T-cell-associated molecule (CRTAM) was identified to show the highest affinity to CADM1 among its binding partners by comparing the dissociation constants calculated from the SPR sensorgrams. These results suggest that the SPRi platform would provide a novel screening tool to characterize extracellular protein–protein interactions among cell surface- and secreted proteins, including IgSF molecules.